mpact of Broken Family upon Adolescents’ Behavior at Secondary Schools in AL- Najaf AL-Ashraf City (Medico Legal Update, 2021)
Background: Broken families It is the family under divorce, separation, death of father, death of motherand death of both parents. It is the legal termination of marriage. It is also the dissolution of marriage thatis contracted between husband and wife by the judgment of a court of competent jurisdiction or by an actof the legislature. Separation and divorce have exclusion and negative effects on the behavior of children aswell as the burden of education for those in charge of it, which involves risks to the psyche and the degreeof coping with children.Objectives: To determine broken families among secondary school adolescents, assess secondary school’sadolescents’ behaviors, determine the impact of broken families on adolescents’ behaviors, and to findout the relationship between adolescent’s behaviors underbroken family and their socio-demographiccharacteristics of age, gender, parent’s education levels, family type and socio-economic status.Methodology: Anon-probability (purposive) sample of (555) students, whose age are between 12 to 18years have been selected; the sampling of study is divided into two stages which include: First stage: theschool’s selection by cluster, the AL-Najaf City divided to six districts, the schools selected randomly (36)school’s boys and girls, from (130) total schools .Second stage: students under broken family selection byusing the purposive sampling, while control group from each school students were randomly selected.Results: Indicate that there is significant relationship between the adolescent’s gender under broken familyand their behavior domain excessive suffering, poor anger control and poor social conformity. While there isa non-significant relationship between the adolescent’s gender under broken family and their other behaviordomains. The results show that there is a highly significant relationship between adolescent’s Educationallevel under broken family and their behavior domain poor impulse control and poor anger control. Whilethere is a non-significant relationship between the adolescent’s Educational level under broken family andtheir other behavior domains.Conclusion: That most of the secondary school’s adolescents under broken family have Behavior problems.Recommendation: To the Governments and Schools should create awareness on the ills of broken homeson the academic, emotional and social adjustments of students through training, workshops and seminars.Parents should be enlightened on the need to stay together as husband and wife to raise a good family